1999
DOI: 10.1364/ao.38.005306
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a high-temperature fiber-optic gas sensor made with a sol-gel process to incorporate a fluorescent indicator

Abstract: To make a gas sensor suitable for use at high temperatures, we have used a sol-gel-processing technique to bond a copper-exchanged zeolite fluorescence indicator onto the end of an all-silica optical fiber. Experimental results from single-fiber prototype sensors show they can be used to measure either the oxygen concentration or the equivalence ratio for gas mixtures containing weak or strong reductants, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 13 publications
1
26
1
Order By: Relevance
“…Remillard and coworkers have shown that a sol gel supported copper based oxygen sensor can be used in a combustion process. [6] With these facts in hand, we anticipate promising results from our design.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Remillard and coworkers have shown that a sol gel supported copper based oxygen sensor can be used in a combustion process. [6] With these facts in hand, we anticipate promising results from our design.…”
Section: Introductionmentioning
confidence: 88%
“…To improve the long-term stability at 200 °C, sensors were prepared by coating optical fibers with 50 and 60 w/w% blends resulting in a more uniform coating, enhanced oxygen quenching, and improved adhesion. Our 3 rd quarter milestone was to: "Complete immobilization of alkali metal salt derivatives of Mo 6 Cl 12 at the tip of a high temperature silica optical fiber.…”
Section: Executive Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Remillard and coworkers have shown that the typical dip-coating technique produced non-uniform silica sol beads on the end of an optical fiber [5]. They devised an interesting approach for applying a sol-gel / fluorophore slurry to the end of an optical fiber.…”
Section: Executive Summarymentioning
confidence: 99%